Modified spectrum-based pushover analysis for estimating seismic demand of dual wall-frame systems. (15th June 2018) - Liu, Yang; Kuang, J.S.; Huang, Qunxian
Highlights: Strong structural interaction exists between wall and frame in wall-frame systems. Most of pushover-based models do not consider the wall-frame interaction. Modified spectrum-based pushover analysis is proposed for wall-frame structures. Case study of wall-frames under different ground-motion intensities is conducted. Results of MSPA show good agreement with nonlinear response time history analysis. Abstract: Although many advanced pushover-based models have been developed for the fast prediction of seismic demand of tall buildings, most of these models are only focused on the analysis of moment-resisting frame structures. The seismic behaviour of dual wall-frame structures is very different from that of a moment-resisting frame structure, as structural walls and frames have totally different deflected shapes under the action of lateral loading, thus resulting in a strong structural interaction between the two load-resisting systems. There are few pushover-based models, in which the different structural responses between structural walls and frame structures are included. In this paper, modification of the spectrum-based pushover analysis (SPA) is presented to consider the structural interaction between shear walls and frames and the different damage modes of a dual wall-frame structure. In the modified spectrum-based pushover analysis (MSPA) method, the force vectors applied to the structure and formulations for determining the total roof displacement are changed to take the wall-frame interaction into account. The applicability and accuracy of MSPA in predicting the seismic demand of dual wall-frame structures are investigated through a case study of four 25-storey reinforced concrete wall-frame structures subjected to different levels of the input ground motions. Comparison of the results from nonlinear response time history analysis (NLRHA), several advanced pushover-based models and the proposed MSPA method has been made. It is seen that only MSPA can predict the distribution of the seismic demand along the height of buildings well, and the seismic demand from MSPA shows very good agreement with that from NLRHA.